The specialized inner ear labyrinth of worm-lizards (Amphisbaenia: Squamata). - Geneva E Clark; Alessandro Palci; Rebecca J Laver; Cristian Hernandez-Morales; Christian A Perez-Martinez; Patrick J Lewis; Monte L Thies; Christopher J Bell; Christy A Hipsley; Johannes Müller; Ricardo Montero; Juan D Daza (PLoS ONE)
High-resolution computed tomography (HRCT) has become a widely used tool for studying the inner ear morphology of vertebrates. Amphisbaenians are one of the most specialized groups of fossorial reptiles but are poorly understood relative to other squamate reptile. In this paper we survey the anatomy of the inner and middle ear of these fossorial reptiles using HRCT models and we describe qualitatively and quantitatively (using 3D morphometrics) the anatomy of the inner ear. Amphisbaenians are diverse in skull anatomy, especially in the configuration of the snout, which correlates with digging modes. We demonstrate that the ear also exhibits a diversity of configurations, which are independent of phylogenetic relationships. Results from morphological analyses also allow us to describe 11 new potentially informative phylogenetic characters including some that help to diagnose amphisbaenians, such as: 1) the globular vestibule, ii) semicircular canals arranged in a circular trajectory, and iii) an extensive area of interaction between the columella footplate and the lagenar recess. Among extant amphisbaenians, Rhineura floridana has the most unusual inner ear configuration, including a horizontal semicircular canal that is in the same orientation as the inclined snout. The new morphological information helps us to better understand the morphology of headfirst-burrowing fossorial reptiles and contributes new data for resolution of phylogenetic relationships among amphisbaenians.